UNCOVERING CULTURAL REPRESENTATION IN AN INDONESIAN EFL TEXTBOOK: A CRITICAL DISCOURSE ANALYSIS FOR PROFESSIONAL COMMUNICATION COMPETENCE - Yulia Tria Hapsari; Ashar Fauzi (Bajang Institute, 2025)
The growing prominence of English as a global lingua franca in professional settings raises concerns about the adequacy of English as a Foreign Language (EFL) textbooks in representing the diversity of World Englishes. This study aims to assess the representation of World Englishes and intercultural awareness in an Indonesian junior high school English as a Foreign Language (EFL) textbook, with a focus on its contribution to enhancing students' professional communication competence. The study employed Critical Discourse Analysis (CDA) to analyze both textual and visual components, alongside the broader social context, to uncover embedded ideologies and power dynamics. The study revealed a primary focus on Inner Circle cultures and Level 1 (Basic Cultural Awareness), with insufficient representation of other English Circles and limited opportunities for critical intercultural engagement. The textbook provides fundamental cultural knowledge but fails to cultivate the intercultural competence required for diverse professional environments. The study signals implications that are examined in relation to textbook developers and teaching practices aimed at enhancing professional communication in a global context